The Relationship Between Characteristics Of Nurse And Their Response Time In Emergency Case In Emergency Unit Of Public Health Care Kumanis Sijunjung In 2016 - Ashra, Fauzi; Amalia, Syafrina (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
Response time is the time between the clients entering the room and request addressed. Response time for the patient is more and less 5 minutes. Long response time can result in a risk of death or severe injury. From the observation data obtained from health centers Kumanis Sijunjung average response time of 5-8 minutes. This study aims to examine the relationship between the characteristics of the nurse and their response time in handling an emergency case in the emergency unit of the health center Kumanis Sijunjung in 2016. This type of research was quantitative with a cross-sectional study. The population in this study was all of the nurses in the emergency unit of health center Kumanis Sijunjung. The Sampling technique was saturated sampling, who was 18 people. The instrument used was observation. The research result showed that there was no relationshipÂ between the age of the nurses and their response time (p-value = 0.02), and there was no relationship between gender and their response time (p-value = 1.000),then, there was no relationship between the education of nurses and their response time (p-value = 0909 ), and there was a relationship between a long working relationship and their response time (p-value = 0.02). Suggestions for emergency unit nurses in order to improve professionalism in serving the availability of human resources and infrastructure affect the speed of services.